Application of additive manufactured polymers in frameworks of full-arch implant-supported fixed prostheses - Antunes, Rafaela Lourenço Graça (2021)
Dissertação de Mestrado Integrado em Engenharia Biomédica apresentada à Faculdade de Ciências e Tecnologia